Unexpected Detection of Anti-SARS-CoV-2 Antibodies Before the Declaration of the COVID-19 Pandemic - Mahallawi, Waleed; Ibrahim, Nadir (Frontiers in Medicine, 2022)
Background No precise data are currently available regarding the global incidence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infections prior to the declaration of the coronavirus disease 2019 (COVID-19) pandemic, which may result in improper conclusions regarding the timing of viral transmission and the origin of the virus. Methods We investigated the presence of specific antibodies against the RBD of SARS-CoV-2 in archived serum samples that were collected from 478 healthy blood donors and patients in Madinah, Saudi Arabia, between October 2019 and January 2020. ELISA was performed to measure SARS-CoV-2 IgM and IgG antibodies. In addition, rheumatoid factor (RF) and urea dissociation tests were performed in all samples, which showed seropositivity for the SARS-CoV-2 IgM antibody. Additionally, Chemiluminescence immunoassays (CLIA) targeting the RBD of the SARS-CoV-2 spike (S) protein were performed to confirm the seropositivity. Results Overall, 20 (4.18%) serum samples containing SARS-CoV-2 IgG or IgM antibodies were detected by ELISA. Of these, 12 (2.51%) samples were positive for IgM antibody, and 8 (1.67%) were positive for IgG antibody. The 12 samples positive for SARS-CoV-2 IgM antibody were subjected to RF and urea dissociation tests, and all samples were RF-negative. The ELISA results were negative for 7 samples when subjected to urea dissociation prior to ELISA, whereas the other 5 samples remained positive. These 5 samples remained positive for the anti-S RBD IgG antibody in the CLIA. In addition, 3 of the 8 samples with IgG positivity according to the ELISA remained positive in the CLIA. After reviewing their data, we discovered that the 8 CLIA-confirmed positive samples were obtained from 3 Saudi and 5 Chinese students who were studying in Saudi Arabia and had visited China during the 4-week period immediately preceding blood donation. Conclusion In conclusion, we found evidence to support the early circulation of SARS-CoV-2 among persons who visited China a few months prior to the pandemic declaration. These results can be used to better define the spread of SARS-CoV-2 infections before the COVID-19 pandemic declaration. The detection of SARS-CoV-2 antibodies in individuals before the pandemic was declared in China could rewrite the pre-pandemic timeline.